Existing Therapeutic Vaccine Approaches for Cervical Cancer - Liu , Shuyang (Transactions on Materials, Biotechnology and Life Sciences, 2024)
As the level of modern medical treatment gradually advances and improves with the development, therapeutic vaccines are gradually being researched and applied in clinical treatment, but there are still some areas that require further research and improvement. This article summarizes the research progress, market development, awareness and popularity of cervical cancer therapeutic vaccines in recent years and treatment scope. The study found that the clinical basis for therapeutic vaccines and their popularity and awareness in remote and low-income developing countries are low, and people in these areas also have misunderstandings about cervical cancer. In addition, the cervical cancer therapeutic vaccine mainly targets HPV16 and HPV18, two subtypes that are the main factors causing cervical cancer. Therefore, there is basically no progress in the research of therapeutic vaccines for cervical cancer except for these two subtypes. The development of therapeutic vaccines for cervical cancer has gradually progressed, but in some places, there are still shortcomings compared with vaccines that are already on the market and are used proficiently.